Cannabis for Medical Use: Versatile Plant Rather Than a Single Drug - Procaccia, Shiri; Lewitus, Gil Moshe; Lipson Feder, Carni; Shapira, Anna; Berman, Paula; Meiri, David (Frontiers in Pharmacology, 2022)
Medical cannabis and its major cannabinoids (−)-trans-Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are gaining momentum for various medical purposes as their therapeutic qualities are becoming better established. However, studies regarding their efficacy are inconclusive. This is chiefly because cannabis is a versatile plant rather than a single drug and its effects do not depend only on the amount of THC and CBD. Hundreds of cannabis cultivars and hybrids exist worldwide, each with a unique and distinct chemical profile. Most studies focus on THC and CBD, but these are just two of over 140 phytocannabinoids found in the plant in addition to a milieu of terpenoids, flavonoids and other compounds with potential therapeutic activities. Different plants contain a very different array of these metabolites in varying relative ratios, and it is the interplay between these molecules from the plant and the endocannabinoid system in the body that determines the ultimate therapeutic response and associated adverse effects. Here, we discuss how phytocannabinoid profiles differ between plants depending on the chemovar types, review the major factors that affect secondary metabolite accumulation in the plant including the genotype, growth conditions, processing, storage and the delivery route; and highlight how these factors make cannabis treatment highly complex.